Copper-64 Chloride Exhibits Therapeutic Potential in Three-Dimensional Cellular Models of Prostate Cancer - Pinto, Catarina I. G.; Bucar, Sara; Alves, Vítor; Fonseca, Alexandra; Abrunhosa, Antero J.; da Silva, Cláudia L.; Guerreiro, Joana F.; Mendes, Filipa (Frontiers in Molecular Biosciences, 2020)
PProstate cancer (PCa) is the second most common cancer type in men, and in advanced metastatic stages is considerable incurable. This justifies the need for efficient early diagnostic methods and novel therapies, particularly radiopharmaceuticals with the potential for simultaneous diagnosis and therapy (theranostics). We have previously demonstrated, using monolayer-cultured cells, that copper-64 chloride, a promising theranostic agent for PCa, has the potential to induce significant damage in cancer cells while having minimal side effects in healthy tissues. Here, we further explored this compound for its theranostic applications using more advanced PCa cellular models, specifically multicellular spheroids. Namely, we evaluated the cellular uptake of 64CuCl2 in three human PCa spheroids (derived from 22RV1, DU145 and LNCaP cells), and characterized the growth profile and viability of those spheroids as well as the clonogenic capacity of spheroid-derived cells after exposure to 64CuCl2. Furthermore, the populations of cancer stem cells (CSCs), known to be important for cancer resistance and recurrence, present in the spheroid models were also evaluated using two different markers (CD44 and CD117). 64CuCl2 was found to have significant detrimental effects in spheroids and spheroid-derived cells, being able to reduce their growth and impair the viability and reproductive ability of spheroids from both castration-resistant (22RV1 and DU145) and hormone-naïve PCa (LNCaP). Interestingly, resistance to 64CuCl2 treatment seemed to be related with the presence of a CSC population, since the most resistant spheroids, derived from the DU145 cell line, had the highest initial percentage of CSCs among the three cell lines under study. Altogether, these results clearly highlight the theranostic potential of 64CuCl2.